Mecanismos de proteção à propriedade intelectual para software - Silva, Nilo Gabriel de Andrade e (2016)
Since the 80s, the growth of the Information Technology sector significantly challenged to create laws for the protection of computer programs. Which are considered an intangible asset and replicable, virtually no cost, it showed the difficulty in creating mechanisms to protect them properly. Thus, it has become evident the need for research aimed at creating efficient legislative frameworks of intellectual property protection for these assets, whether constituting them as a stimulus instruments to innovation, not allowing laws may create obstacles to the spread of knowledge in society. In this sense, the present study aimed to analyze the protection model adopted in Brazil, its evolution and the inherited influence of the United States and Europe. To this end, a historical review of international and Brazilian legislation was carried out, which showed complex dilemmas surrounding this issue in the framework of legality worldwide. Then a regulatory review was presented, addressing the software 'and' computer program, the types of software and legislation has been applied in the present scenario. Soon after, a detailed analysis of software registration by copyright and by industrial law was held. The first, contemplanado topics related to the computer program protection itself, the protection of literal and non-literal elements, protection documentation, term of protection, limits of protection and protection functionality. Subsequently, the work presented an overview of the use of the intellectual property system for computer program in Brazil and Sergipe. Finally, a case study related to the registration of software was presented in order to demonstrate how this mechanism in practice, since the prospect of technology, to the procedures to be followed for registration with the INPI. It was found in this work that national legislation has yet to move forward in order to properly organize the conflicts and the needs of the information technology industry. As a result, there was a practical process of disordered legal interpretations and inconsistent, showing that those involved in intellectual property issues, whether they are in academia, government institutions and companies, need to promote new studies and intensify this kind of debate, aiming harmonize common interests and enable the economic and technological development of the country.